Human Resource Development Practices and Employee Engagement in Nepalese Commercial Banks - Niraula, Ganesh Prasad; Kharel, Shreekrishna (Saptagandaki Journal, 2023)
The level of employee engagement is a significant issue for many organizations globally. As a result, many organizations are using a variety of human resource development practices to enhance employee engagement. The purpose of this study is to focus on analyzing the relationship between HRD practices and employees' engagement in Nepalese commercial banks. The study's independent variables were Career Advancement, Performance Management. Reward and Recognition and Training and Development. The dependent variable is Employee Engagement. The descriptive research design is used. The population of the study was 46408, and a simple random sampling technique was used to pick 384 employees from 11 commercial banks as sample. Data were gathered by using a standardized questionnaire on Likert Scale with 1 specifying a strongly disagree and 5 a strongly agree. Descriptive statistics such as Mean, Correlation and Regression were employed to analyze the data. Chronbach's Alpha was used to test the reliability. Which was 0.65 on an average. SPSS version 26 was used to analyze the data. The study concluded that Career Advancement and Performance Management had a favorable and significant relationship with Employee Engagement, Reward and Recognition and positive but insignificant relationship and Training and Development had a negative but significant relationship with Employee Engagement.